2013
DOI: 10.1523/jneurosci.0174-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain: Lost Inhibition?

Abstract: Human brain imaging has revealed that acute pain results from activation of a network of brain regions, including the somatosensory, insular, prefrontal, and cingulate cortices. In contrast, many investigations report little or no alteration in brain activity associated with chronic pain, particularly neuropathic pain. It has been hypothesized that neuropathic pain results from misinterpretation of thalamocortical activity, and recent evidence has revealed altered thalamocortical rhythm in individuals with neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
137
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 53 publications
19
137
2
1
Order By: Relevance
“…Recent proton MRS studies identified permanently decreased GABA concentrations and altered Glu or Glx levels compared to healthy controls indicating impairments in neurotransmission (Harris and Clauw, 2012;Henderson et al, 2013). However, since these measurements were performed under resting state conditions only, they are unable to differentiate between changes solely reflecting disordered neuronal regulations or being also related to degenerative cellular changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent proton MRS studies identified permanently decreased GABA concentrations and altered Glu or Glx levels compared to healthy controls indicating impairments in neurotransmission (Harris and Clauw, 2012;Henderson et al, 2013). However, since these measurements were performed under resting state conditions only, they are unable to differentiate between changes solely reflecting disordered neuronal regulations or being also related to degenerative cellular changes.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic pain, studies with PET [58-61] and arterial spin labeling MRI [62-65] show increases of blood flow and metabolism in prefrontal, cingulate, and insular cortices and in the striatum as well as decreases in the thalamus. Some of these blood flow changes positively relate to pain intensity (e.g.…”
Section: Brain Structure and Function In Tinnitus And Chronic Painmentioning
confidence: 99%
“…Molecular and functional studies on humans and animal models have shown that several brain areas, such as the periaqueductal grey (Baliki et al, 2014;Palazzo et al, 2012), the anterior cingulate cortex (Barthas et al, 2015;Rainville et al, 1997), the prefrontal cortex (Metz et al, 2009;Zhang et al, 2004) and the thalamus (Baliki et al, 2014;Henderson et al, 2013) are involved in pain processing.…”
Section: Introductionmentioning
confidence: 99%